2000
DOI: 10.1046/j.1439-0272.2000.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Male adolescent exposure to endocrine-disrupting pesticides: vinclozolin exposure in peripubertal rabbits

Abstract: Adolescence is a time of dramatic neuroendocrine changes that are required for sexual maturation. Hormonal mimicking or inhibiting chemicals can cause significant impairment during this critical period. Vinclozolin (Vin) has been shown to be an anti-androgen affecting male offspring in rats in utero, and its mechanism of action may be mediated by inhibition of androgenic receptor action. The majority of teenagers working on farms are male, and therefore a systemic fungicide, vinclozolin, was selected for study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Decreases in accessory sex organ weights including epididymis, prostate, and seminal vesicle by VCZ or FLU treatment were in agreement with those in other studies reported previously [1,[7][8][9]. In general, treatments of an antiandrogen induce a microscopic alteration in the testis of rats, commonly characterized by hypertrophy of Leydig cells [1,7].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Decreases in accessory sex organ weights including epididymis, prostate, and seminal vesicle by VCZ or FLU treatment were in agreement with those in other studies reported previously [1,[7][8][9]. In general, treatments of an antiandrogen induce a microscopic alteration in the testis of rats, commonly characterized by hypertrophy of Leydig cells [1,7].…”
Section: Discussionsupporting
confidence: 91%
“…These results in the present study indicate that the treatment of antiandrogen for ten consecutive days during puberty in male rats could affect sperm counts of cauda epididymis in adulthood. Moorman et al [8] reported a controversial result that showed an increased count of pooled sperms in the rabbit. The reason for the discrepancy is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential problem is that hydrolytic products 2-[[(3,5-dichlorophenyl)-carbamoyl]oxy]-2-methyl-3-butenoic acid (M1) and especially 3 0 ,5 0 -dichloro-2-hydroxy-2-methylbut-3-enanilide (M2) effectively compete with endogenous androgens for androgen receptor (K i vs R1181 (methyltrienolone) of more than 700, 92 and 9.7 mM for vinclozolin, M1 and M2; Kelce et al 1994), and block the desired response. Both M1 and M2 are formed in rats and rabbits , Moorman et al 2000, and accumulate in soil, plants, and animals. There is a paucity of information on human exposure to metabolites of vinclozolin.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to effects on spermatogenesis, there is a report demonstrating a decrease in the number of sperm in F1 male rats due to maternal administration of vinclozolin at high doses of 100 mg/kg and above Gray et al, 1994). On the other hand, an increase in the number of sperm due to administration of vinclozolin to rabbits during sexual maturation has also been reported (Moorman et al, 2000). The blood concentrations of LH, FSH, testosterone, and DHT rose to nearly the same extent in F0 and F1 males in this study.…”
Section: Effects On Reproductive Functionmentioning
confidence: 99%